2022
DOI: 10.1021/acs.est.2c07418
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dimethylarsenate to Highly Toxic Dimethylarsenite in Paddy Soil and Rice Plants

Abstract: Dimethylarsenate [DMAs(V)] is a common methylated As species in soils and plants and can cause the physiological disorder straighthead disease in rice. Because DMAs(V) is relatively noncytotoxic, we hypothesize that phytotoxicity of DMAs(V) may arise from trivalent dimethylarsenite [DMAs(III)]. DMAs(III) has been detected in human urine samples but not in environmental samples, likely due to its instability under oxic conditions. We first established methods for preservation and detections of DMAs(III) in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Recently, we reported that a M. luminyensis CZDD1 coculture with C. malenominatum CZB5 produced CH 4 from DMAs (V) but the monoculture did not ( 29 ). It was also found that C. malenominatum CZB5 reduced DMAs (V) to DMAs (III), which is a highly toxic ( 30 ). Given that EET promoted a high rate of methanogenesis by M. luminyensis CZDD1 (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we reported that a M. luminyensis CZDD1 coculture with C. malenominatum CZB5 produced CH 4 from DMAs (V) but the monoculture did not ( 29 ). It was also found that C. malenominatum CZB5 reduced DMAs (V) to DMAs (III), which is a highly toxic ( 30 ). Given that EET promoted a high rate of methanogenesis by M. luminyensis CZDD1 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These demonstrated that DIET with C. malenominatum CZB5 and EET supported higher rates of methanogenesis by M. luminyensis CZDD1 than H 2 . Importantly, both DIET and EET but not H 2 enabled methanogenesis from DMAs, a toxic chemical that causes straight-head rice disease ( 30 ). Based on differential transcriptomic analysis, the EET-based methanogenic pathway and energy metabolism mode was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Various PC-As(III) complexes have been identified in plants (Raab et al, 2005;Liu et al, 2010a;Mishra et al, 2013). In contrast, there is no evidence in the above studies for the presence of PC-DMAs complexes, even though dimethylarsenate [DMAs(V)] can be partially reduced to the more toxic dimethylarsenite [DMAs(III)] in rice plants (Chen et al, 2022a). The lack of PC complexation of DMAs explains why the PC detoxification mechanism is ineffective for DMAs (Tang et al, 2016).…”
Section: Complexationmentioning
confidence: 99%
“…In Arabidopsis, AtHMA4 ( HEAVY METAL ATPASE 4 ) promotes loading Zn and Cd into the xylem vessels in the root system and, its overexpression in tobacco increased Zn and Cd concentrations in shoots and improved the efficiency of metal root‐to‐shoot translocation (Barabasz et al, 2016). Mutation in OsCADT1 , a serine hydroxymethyl transferase, boosted Cd tolerance in rice by increasing PC production via metabolic changes in the sulfur assimilation pathway (Chen et al, 2022a). Overexpression of radish RsMYB1 in petunia enhanced the expression of genes related to metal detoxification [glutathione S‐transferase (GST) and phytochelatin synthase (PCS)] and antioxidant activity (SOD, CAT, and POX).…”
Section: Genetic Engineering Tools Help Fast‐track the Tolerance Agai...mentioning
confidence: 99%